Coaching unified sports: associations between perceived athlete improvement, barriers, and coach attitudes across five European countries - Maciej Wilski; Piotr Urbański; Roxana Ossian; Gabriela Papp Eniko; Nina Bracanovic Milovic; Ivan Radovic; Veronica Sedlackova; Eva Gazova; Nadira Sabanovic; Kada Delic Selimovic; Velibor Srdic; Srboljub Vukovic; et al. (Frontiers in Psychology, 2025)
PurposeThis study aimed to examine how perceived athlete improvement, perceived barriers to implementation, and selected coaching characteristics are associated with coaches’ attitudes toward Unified Sports programs. The investigation focused on understanding the psychological and contextual factors that influence inclusive coaching engagement within a multi-country sample, rather than comparing national differences directly.MethodsA cross-sectional survey was conducted with 102 coaches involved in Unified Sports programs in five European countries. Participants completed a standardized questionnaire assessing their attitudes toward inclusion, perceived improvement in athletes with developmental disabilities and their non-disabled partners, perceived implementation barriers, and personal coaching background. Hierarchical multiple regression analysis was used to identify predictors of coaching attitudes.ResultsPerceived improvement in athletes with developmental disabilities was the strongest and most consistent predictor of positive coaching attitudes. Coaches who reported greater perceived progress in these athletes were more likely to endorse inclusive beliefs. In contrast, perceived improvement in non-disabled partners, although generally rated highly, did not significantly predict coaching attitudes. Interestingly, coaches with prior experience working in disability sports and those with familial relationships to participating athletes expressed more skeptical views, suggesting that emotional involvement or cumulative exposure may introduce attitudinal strain. Although institutional, social, and logistical barriers to Unified Sports were widely recognized by participants, these factors did not independently predict attitudes once other variables were controlled for.ConclusionThe findings underscore the motivational role of observed progress among athletes with disabilities in shaping coach engagement and suggest that experiential factors such as previous involvement and personal ties may carry unanticipated emotional or structural challenges. These insights point to the importance of designing coach education and support programs that not only promote technical competence but also address emotional resilience and contextual demands. Strengthening these components may enhance the sustainability and effectiveness of Unified Sports initiatives worldwide.